Renaissance drama : an anthology of plays and entertainments - Kinney, Arthur F. (Blackwell anthologies., 1999)
"This pioneering collection of non-Shakespearean Renaissance drama is the first ever to cover the full sweep of dramatic performances in the England Shakespeare knew. Newly edited from manuscript and quarto, all the major playwrights are here - Marlowe, Jonson, Middleton, Webster - as well as new dramatic scripts and plays published for the first time.